2010
DOI: 10.1002/ls.127
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic analysis, regularisation and stable numerical solutions for heavily loaded line EHL contacts

Abstract: An analytical analysis of a line thermal EHL contact under heavily loaded conditions is proposed. The analysis is based on regular matched asymptotic expansions. In particular, a case of relatively small ratio of rolling and sliding frictional stresses is considered. The problem is reduced to an analogue of the isothermal EHL problem by eliminating lubricant temperature from the problem formulation. The further asymptotic and numerical analysis is very similar to the case of the isothermal EHL problem. THERMAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…The aforementioned systems of asymptotic equations in the inlet and exit zones are very similar to the ones derived and analysed for the cases of line EHL contacts in . Namely, by introducing the substitutions centercenter{},rsα1β1=1r0{}rpspα1pβ1p,{},qg=1N0r01/2{}qpgp,center{},hqhg=1h{}hitalicqphitalicgp,{}μq()q,μg()g={}μqp()qp,μgp()gp,and the definitions A=Ap[]θN04()y1/5hy,H0y=H00hy,r0=[]θ2N03()y2/5we will be able to reduce each of the aforementioned systems of asymptotically valid equations to centercenterA3+1r()+1hq3μq+1qr=+12πtrue0q(),tyqa(),tytr…”
Section: Asymptotic Analysis Of a Heavily Loaded Lubricated Contact Umentioning
confidence: 84%
See 1 more Smart Citation
“…The aforementioned systems of asymptotic equations in the inlet and exit zones are very similar to the ones derived and analysed for the cases of line EHL contacts in . Namely, by introducing the substitutions centercenter{},rsα1β1=1r0{}rpspα1pβ1p,{},qg=1N0r01/2{}qpgp,center{},hqhg=1h{}hitalicqphitalicgp,{}μq()q,μg()g={}μqp()qp,μgp()gp,and the definitions A=Ap[]θN04()y1/5hy,H0y=H00hy,r0=[]θ2N03()y2/5we will be able to reduce each of the aforementioned systems of asymptotically valid equations to centercenterA3+1r()+1hq3μq+1qr=+12πtrue0q(),tyqa(),tytr…”
Section: Asymptotic Analysis Of a Heavily Loaded Lubricated Contact Umentioning
confidence: 84%
“…According to , the two systems in and can be rewritten in the equivalent form as follows: centercenterq(),ry=2r[]112πtrue0tM0qhqμqtydt2ttr,centerq(),ryqa(),ry=2r+α1()y2r,bold-italicr,centerA3=πα1/true0thq3μqqtytdt2t,centerhq(),ry=1bold-italicorbold-italicA[]hq(),ry1=2πtrue0qtyqatyln1trdt, centercenterg(),sy=2s[]112πtrue0tM0…”
Section: Asymptotic Analysis Of a Heavily Loaded Lubricated Contact Umentioning
confidence: 99%
“…The numerical results include parametric studies, studies of solution precision and stability and so on. On the basis of the fact that the asymptotically valid equations for the EHL problem with skewed lubricant entrainment can be reduced to equations identical to the asymptotically valid equations for the EHL problem with straight lubricant entrainment analysed and described in detail in here due to the limited space, these studies are not presented.…”
Section: Asymptotic Analysis Of a Heavily Loaded Lubricated Contact Umentioning
confidence: 99%
“…It has been shown that by a simple transformation, the derived equations can be reduced to equations identical to the corresponding equations for pre‐critical lubrication regimes in the inlet and exit zones of line heavily loaded contacts. The latter equations have been validated through the comparison with the direct numerical solutions of the original EHL equations in . For over‐critical lubrication regimes, another approach has been used, which led to formulas for the lubrication film thickness for starved and fully flooded conditions.…”
Section: Closurementioning
confidence: 99%
See 1 more Smart Citation